กลยุทธ์การบริหารความร่วมมือทางสังคมออนไลน์เชิงสร้างสรรค์ในการศึกษาสำหรับโรงเรียนเอกชนระดับอนุบาลในเขตกรุงเทพมหานคร - บุณยรักษ์ รุ่งรุจน์ธนัน; สินลารัตน์ ไพฑูรย์; วิเศษศิริ ปองสิน (Journal of Education Studies, Chulalongkorn University, 2019)
The purpose of this research was to 1) investigate the current and potential problems of cooperation management, 2) develop creative online social cooperation strategy management in education for a private kindergarten in the Bangkok Metropolitan area. Mixed methods research was conducted and the population of this research consisted of 128 private kindergarteners in Bangkok. The data collection instruments used were questionnaires, in-depth interviews and the strategic evaluation form of feasibility and appropriateness. The data were analyzed in terms of content analysis, frequency distribution, percentage, mean, standard deviation and PNI Modified The results of this study indicated that 1) despite the high level of the current and potential problems of cooperation management, the main potential problem was allowing parents’ participation in the cooperation management aspect; 2) the creative online social cooperation strategy consists of: 2.1) the co-creation of value through social media, 2.2) the co-creation of integrating the plan and implementation effectively, 2.3) rapid knowledge co-creation through heterogeneous interaction.